(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Every year there are several hundred tons of waste glass produced in Latvia. Glass can be re-used as a fine raw material and it presents a possibility to save natural, non-renewable materials. The use of glass powder in concrete production can make the construction industry more environmentally friendly. This paper examines the possibility of using glass powder as cement replacement in a new type of concrete. In the experiment, cement was partially (20% and 40%) replaced with glass powder. The long-term deformation (creep) of this new concrete was monitored. Three different concrete mixtures were batched. Specimens of 20% and 40% cement replacement were compared with the specimens made of standard concrete. The samples were tested in two extreme conditions: in one case they were kept in 100% humidity ensured by preventing the desiccation of the concrete, and in the other case samples were air-dried by preventing them from becoming wet. Compression strength and modulus of elasticity of 7 and 28 days old cubic samples was determined.